Emancipated party members: Examining ideological incongruence within political parties. (January 2017) - Kölln, Ann-Kristin; Polk, Jonathan
Party members across European democracies exercise increasing influence on parties' policy platforms or personnel choices. This article investigates ideological (in)congruence on the left–right spectrum between members and their parties by drawing on a party membership survey of more than 10, 000 individuals across seven political parties in Sweden. The results show that around two-thirds of members are not perfectly congruent with their party. In a two-step analysis, the article argues that emancipated members, with higher political interest and with a more independent self-conception, are more comfortable being ideologically incongruent with their party. We also provide evidence that ideological incongruence matters for members' exit, voice and loyalty behaviour. It is associated with a more negative evaluation of the party leader (voice) and with a higher probability to either vote for another party (loyalty) or even to leave the current one (exit). The findings indicate that ideological incongruence within parties is not a trivial matter, but is rather substantial in size with potentially important consequences for party competition.